2017
DOI: 10.1155/2017/4517486
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Inhibits Glutamate‐Induced Oxidative Toxicity through Prevention of Mitochondrial Dysfunction and Suppression of MAPK Activation in SH‐SY5Y Human Neuroblastoma Cells

Abstract: Glutamate excitotoxicity is associated with many neurological diseases, including cerebral ischemia and neurodegenerative diseases. Tanshinone IIA, a diterpenoid naphthoquinone from Salvia miltiorrhiza, has been shown to suppress presynaptic glutamate release, but its protective mechanism against glutamate-induced neurotoxicity is lacking. Using SH-SY5Y human neuroblastoma cells, we show here that excessive glutamate exposure decreases cell viability and proliferation and increases LDH release. Pretreatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 60 publications
3
42
0
Order By: Relevance
“…Tanshinone IIA is a natural diterpene quinone isolated from the roots of Salvia miltiorrhiza Bunge that has been used as a traditional Chinese medicine for promotion of blood circulation and relieving vessel stasis [ 20 ]. Previous studies have further shown that tanshinone IIA is effective for treating coronary, cerebrovascular, and cardiovascular diseases [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tanshinone IIA is a natural diterpene quinone isolated from the roots of Salvia miltiorrhiza Bunge that has been used as a traditional Chinese medicine for promotion of blood circulation and relieving vessel stasis [ 20 ]. Previous studies have further shown that tanshinone IIA is effective for treating coronary, cerebrovascular, and cardiovascular diseases [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant characteristics of achillolide A demonstrated in this study in Aβ-treated N2a neuroblastoma cells support our previous observations, showing similar effects in glutamate-treated neuroblastoma N2a cells [ 22 ], H 2 O 2 -treated astrocytes and LPS-activated microglial cells [ 20 , 24 ]. Although part of Aβ toxicity is mediated by glutamate [ 27 ], the mechanism underlying Aβ cytotoxicity is complex and involves many downstream targets (for review see [ 28 ]). As neuronal vulnerability in AD originates in the hippocampal formation, future experiments should examine the effect of achillolide A on these neuronal populations in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…We have showed that the PMV-CD36 complex activates MKK4/JNK2 signals and contributes to platelet activation [11]. Earlier studies demonstrated that TS IIA can reduce oxidative stress and regulate apoptosis by suppressing JNK and p38 MAPK activation [19]. Nevertheless, the effect of TS IIA on platelet MAPK signal pathways is unknown.…”
Section: Discussionmentioning
confidence: 98%